The mental health of the hearing impaired in Jeddah during the Coronavirus - Alsubaie, Norah Dakhilallah; Baamer, Manal Yahia (Journal of Educational and Psychological Sciences, 2023)
This study aimed to reveal the level of mental health of people with hearing impairment during the Corona pandemic, and the study sample consisted of (35) people (17 males, 18 females) in Jeddah in 2021, The researcher used the descriptive approach as well as the measure of the level of mental health of Sayed Youssef, consisting of (15) phrase. The results of the study concluded that the level of mental health was high among those with hearing impairment, and that there were no statistically significant differences in the level of mental health attributable to sex. The researcher recommended conducting more research on the level of mental health with some variables such as age and marital status and conducting more studies on other groups of people with special needs.